Cultural History, the Possible, and the Principle of Plenitude - Salmi H (WILEY-BLACKWELL, 2022)
The article argues that the study of past cultures always entails the mapping of past possibilities. The first strand of the essay builds on the metaphor of the black hole and intends to solve one of the central problems faced by cultural historians, namely, how to access the horizon of the people of the past, their experience of their own time, especially when the sources remain silent. The second, more speculative strand builds on the notion of plenitude and is designed to open up avenues for further discussion about the concept of culture in particular.